Metahuman KAGURI 0.1 as The Learning Media Innovation for Local Arts and Culture Exploration - Aquita Valentina; Welly Suryandoko; Autar Abdillah (JINoP (Jurnal Inovasi Pembelajaran), 2025)
This research aims to create a learning media utilising Metahuman technology, named "KAGURI 0.1”, to delve into the local arts of Bangil, Pasuruan. This media aims to introduce, safeguard, investigate, and enhance students' appreciation for the diverse local arts found in Bangil. The research employed a Research and Development (R&D) approach. During the analysis phase, a field study was performed to assess the learning requirements for arts and culture, alongside exploring various local art forms in Bangil, Pasuruan. The design phase consisted of planning the learning media, which included crafting storylines and user interaction scenarios. The development phase entailed generating representative metahuman characters using the "Metahuman Creator" software from Unreal Engine 5. Subsequently, the implementation phase involved integrating the media into the educational context and evaluating it with actual junior high school student groups. Evaluation was conducted through assessments of effectiveness and quality, including evaluations of language, graphics, content, user engagement, and learning efficacy. Findings from the study reveal that the Metahuman KAGURI 0.1 learning media was effectively crafted as an interactive tool that amalgamates visual, auditory, and interactive components in the study of arts and culture, particularly focused on the local arts of Bangil. This research carries several implications, such as bridging digital and traditional learning, promoting the preservation and sharing of cultural heritage, fostering immersive learning experiences, and most importantly, positively influencing our future generations.